2011
DOI: 10.1128/ec.05025-11
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Localization, Essentiality, and High-Resolution Crystal Structure of Glucosamine 6-Phosphate N -Acetyltransferase from Trypanosoma brucei

Abstract: A gene predicted to encode Trypanosoma brucei glucosamine 6-phosphate N-acetyltransferase (TbGNA1; EC 2.3.1.4) was cloned and expressed in Escherichia coli. The recombinant protein was enzymatically active, and its high-resolution crystal structure was obtained at 1.86 Å. Endogenous TbGNA1 protein was localized to the peroxisome-like microbody, the glycosome. A bloodstream-form T. brucei GNA1 conditional null mutant was constructed and shown to be unable to sustain growth in vitro under nonpermissive condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 56 publications
1
30
0
3
Order By: Relevance
“…Short-term interruption already leads to arrest of growth in heterotrophic organisms when no external GlcNAc source is supplied as was shown for Trypanosoma brucei [9]. Short-term interruption already leads to arrest of growth in heterotrophic organisms when no external GlcNAc source is supplied as was shown for Trypanosoma brucei [9].…”
Section: Figure 1 Reaction Schemementioning
confidence: 79%
“…Short-term interruption already leads to arrest of growth in heterotrophic organisms when no external GlcNAc source is supplied as was shown for Trypanosoma brucei [9]. Short-term interruption already leads to arrest of growth in heterotrophic organisms when no external GlcNAc source is supplied as was shown for Trypanosoma brucei [9].…”
Section: Figure 1 Reaction Schemementioning
confidence: 79%
“…cruzi ( S1 Fig ) and have recently been shown to be essential for blood stage T . brucei [ 17 ]. The targeted deletion of the L .…”
Section: Resultsmentioning
confidence: 99%
“…The survival strategies of protozoan parasites frequently involve the participation of glycoconjugates. In the particular case of T. brucei , several precursors required for the biosynthesis of these glycoconjugates such as UDP-Gal and UDP-GlcNAc ( Roper et al 2002 , 2005 ; Stokes et al 2008 ; Marino et al 2011 ) are essential for the survival of the parasite in the bloodstream and/or procyclic form life stages. This prompted us to mine the T. brucei genome for UDP-sugar-dependent GTs and to investigate their essentiality, function and specificity by the creation of null or conditional null mutants.…”
Section: Discussionmentioning
confidence: 99%
“…The creation of UDP-glucose 4′-epimerase ( TbGalE ) conditional null mutants showed that this gene, and hence UDP-Gal, is essential for the survival of the parasite in both the bloodstream and procyclic life stages ( Roper et al 2002 ; Roper et al 2005 ; Urbaniak et al 2006 ). Similarly, the creation of UDP-GlcNAc pyrophosphorylase ( TbUAP ) and glucosamine 6-phosphate N -acetyltransferase ( TbGNA1 ) conditional null mutants has shown that UDP-GlcNAc is also essential for bloodstream form T. brucei ( Marino et al 2011 ; Stokes et al 2008 ). From these experiments, it is possible to conclude that one or more of the UDP-Gal- and UDP-GlcNAc-dependent glycosylation pathways are essential to the parasite.…”
Section: Introductionmentioning
confidence: 99%